Introduction of The Tilawati Method to Increase Early Childhood Interest in Learning Hijaiyah Letters - Tini Nazahwa; I. Ismail (Golden Ratio of Data in Summary, 2026)
Early childhood learners tend to prefer engaging and interactive activities. However, in some kindergartens (TK), the teaching of Hijaiyah letters still relies on conventional methods that are less attractive, resulting in low learning interest among children. This study aimed to examine the effect of introducing the Tilawati moethod on increasing early childhood learners’ interest in learning Hijaiyah letters. The research employed a Classroom Action Research (CAR) approach, with 16 children aged 5–6 years at TK Putra Bangsa as the subjects. The research procedures included planning, action implementation, observation, and reflection over two cycles. The instruments used were observation sheets for children’s learning interests and documentation. The results showed that after implementing the Tilawati method, children’s interest in learning Hijaiyah letters increased significantly. In Cycle I, 40% of the children showed high interest, which increased to 86.67% in Cycle II. The study concluded that the Tilawati method, which combines songs and games, can effectively enhance early childhood learners’ interest in learning Hijaiyah letters. It is recommended that kindergarten teachers integrate the Tilawati method into the teaching of Hijaiyah letters to make the learning process more enjoyable and effective.